Evaluation of HBV-DNA Monitoring after Completion of Chemotherapy using a PDCA Cycle following Introduction of a Support System Provided by a Multidisciplinary Team of Quality Management in Cancer Medicine (Journal of Cancer Research Updates, 2025)
Background: Reactivation of the hepatitis B virus (HBV) during or after chemotherapy remains a notable clinical concern, particularly among patients with previous exposure to HBV. However, in clinical practice, adherence to HBV-DNA monitoring after completing chemotherapy is often sub-optimal.Methods: We developed and implemented a support system based on the plan–do–check–act (PDCA) cycle to ensure 12-month HBV-DNA monitoring after the completion of chemotherapy. This system was designed to enable continuous follow-up after a cessation of chemotherapy, and a multidisciplinary team of quality management in cancer medicine established a feedback system to provide timely information for physicians. Adherence to HBV-DNA monitoring before and after introduction of the system was compared, and the reasons for discontinuation were investigated.Results: Compared with the pre-intervention group, there was a significant improvement in the rate of HBV-DNA monitoring in the post-intervention group (p < 0.01). In this group, 16 patients (33.3%) were lost to follow-up after chemotherapy due to death or transition to hospice or home-based care.Conclusions: The support system provided by a multidisciplinary team of quality management in cancer medicine effectively improved adherence to HBV-DNA monitoring after the completion of chemotherapy. However, it also revealed that some patients could not be followed up immediately after the completion of treatment given their deteriorating general condition.